Pengaruh Bimbingan Guru Pendidikan Agama Kristen Terhadap Disiplin Siswa Kelas IX SMP Negeri 5 Sitapongan Tahun Pelajaran 2023/2024 - Ira Tripena Silalahi; Simion D Harianja; Risden Anakampun; Dorlan Naibaho; Pestaria Naibaho (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The study aims to determine the effect of Christian Religious Education teacher guidance on the discipline of ninth grade students of SMP Negeri 5 Sitapongan in the 2023/2024 academic year. The research hypothesis is that there is a positive and significant influence between the guidance of Christian Religious Education teachers on the discipline of ninth grade students of SMP Negeri 5 Sitapongan in the 2023/2024 academic year. Descriptive quantitative research method. The population of all ninth grade students of SMP Negeri 5 Sitapongan in the 2023/2024 academic year who are Protestant Christians is 102 people. Sampling from the list of estimated sample sizes based on the Krejcie Morgan formula is 80 people. The research instrument was a closed questionnaire. The results of data analysis obtained: 1) regression equation. 2) The determination test found the influence of 28.30%. 3) Hypothesis testing obtained thitung = 3,181>ttabel = 2,000, namely there is a positive and significant influence between the guidance of Christian Religious Education teachers on student discipline in class IX SMP Negeri 5 Sitapongan in the 2023/2024 academic year and can be accepted as true.